2015
DOI: 10.1097/tp.0000000000000312
|View full text |Cite
|
Sign up to set email alerts
|

Three-Year Outcomes Following 1420 ABO-Incompatible Living-Donor Kidney Transplants Performed After ABO Antibody Reduction

Abstract: In this analysis of prospectively collected data from a large series of ABO-incompatible living-donor kidney transplants performed at 101 centers, death-censored graft and patient survival rates were similar to those achieved in ABO-compatible control groups over the same period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 16 publications
15
133
1
1
Order By: Relevance
“…No antibody-mediated rejection occurred during our follow-up period, and the rate of acute cellular rejection was 14.3% (2/14) in this study. A previous large-sized, multicenter study revealed that the frequency of rejection treatment was 16.3% in ABO-incompatible kidney transplantation [27], which was similar to our rate of acute cellular rejection.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…No antibody-mediated rejection occurred during our follow-up period, and the rate of acute cellular rejection was 14.3% (2/14) in this study. A previous large-sized, multicenter study revealed that the frequency of rejection treatment was 16.3% in ABO-incompatible kidney transplantation [27], which was similar to our rate of acute cellular rejection.…”
Section: Discussionsupporting
confidence: 68%
“…Meanwhile, previous reports have shown that the administration of rituximab induces proinflammatory cytokines releases associated with regulatory B cell depletion. However, in ABO-incompatible kidney transplantation, any cytokine release would have been resolved by plasmapheresis and administration of steroid before transplantation [27]. Previously, we showed that acute cellular rejection in ABO-incompatible kidney transplant recipients receiving rituximab might be associated with late-onset neutropenia due to B cell-related cytokine release [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…However, ABO-incompatible (ABOi) renal transplantation has become more popular and hundreds of patients have been successfully transplanted across the ABO-barrier [32][33][34]. Infants have low levels of ABO-antibodies and are immunologically good candidates for ABOi-transplantation.…”
Section: Donor Characteristicsmentioning
confidence: 99%
“…As shown in Table 5, ABOi patients had lower levels of Hb and platelets in the early post-KT period (P = 0.02, P = 0.0001, respectively), but there was no statistical difference by the end of the 24-month follow-up: i.e., 13.8 for ABOi ± 1.7 versus 13 ± 1.7 g/ dL for the ABOc group for Hb, and 202.7 ± 46.4 for ABOi versus 204.6 ± 67.7×10 3 /mm 3 for the ABOc group for platelets. Amongst all peripheral lymphocytes, there were lower proportions of lymphocyte CD19 in the early post-KT period in ABOi recipients (1.5±2.1 in the ABOi group vs. 14.3±19.5% in the ABOc group, P=0.002); these results correspond to use of rituximab in ABOi recipients.…”
Section: Hematological Characteristics Throughout the 24-month Followmentioning
confidence: 99%
“…However, the lack of deceased donors and the increasing numbers of patients with ESRD and on a KT waiting-list has caused long waiting times for a suitable allograft (3). For this reason a living-donor KT becomes an important option (4).…”
Section: Introductionmentioning
confidence: 99%